Object extraction is not subject to Child Relativized Minimality - Goodluck, Helen (Lingua, 2010)
Friedmann et al. (2009) propose that the grammar of three–five-year-old children imposes a stricter version of Relativized Minimality that the adult grammar does. This allows them to explain several experimental findings, including the difficulty children have in comprehending object relative clauses when the subject of the relative is a lexical NP, and in comprehending object questions when the object is D(iscourse)-linked. The purpose of this paper is to challenge their analysis, in terms of both its empirical coverage and its implications for a theory of acquisition that assumes continuity.